A VIRUS-INDUCED MAMMALIAN GROWTH WITH THE CHARACTERS OF A TUMOR (THE SHOPE RABBIT PAPILLOMA) : I. THE GROWTH ON IMPLANTATION WITHIN FAVORABLE HOSTS - Rous, Peyton (The Rockefeller University Press, 1934)
Rabbit papillomas developing on the skin as the result of virus inoculation can be readily transferred to the inner organs of favorable hosts by implanting bits of the living tissue. The growths thus produced proliferate actively as a rule and frequently cause death. Often they are markedly invasive and destructive; and they tend to recur after excision. Bacterial infection may greatly enhance their malignancy. Accidental dissemination may occur during operation, and distribution to the peritoneal surface has been repeatedly noted. There may be no cellular reaction whatever about the invading epithelium of interior growths, but usually some new formation of connective tissue takes place, its amount varying inversely with the rate of epithelial proliferation. An immediate reason exists for the inflammatory changes and scarring found beneath long-established skin papillomas, in the trauma and secondary infection to which the projecting, necrotizing masses have been subjected. In animals dying of progressively enlarging interior growths the skin papilloma may long have been stationary in size. The growths appearing after the transfer of papillomatous tissue to the inner organs are due to the survival and multiplication of transplanted cells. However, the virus can be readily recovered from them, in the case of wild rabbits. No distinctive changes in the blood of the host have been found. The virus itself is highly specific for the epithelium of the skin, failing to act not only upon that of the other organs thus far tested but even upon embryonic skin. The papilloma frequently penetrates into the blood and lymph vessels, especially at the edge of implantation growths. The intravascular injection of fragments of it sometimes results in pulmonary nodules of characteristic morphology. These are due to survival and proliferation of the injected cells. Secondary nodules have been encountered at autopsy in a lymph gland and in the lungs, but under conditions more suggestive of operative dissemination of the growth than of true metastasis. Implantation growths of the papilloma in favorable hosts have the morphology of epidermoid tumors of greater or less malignancy. They behave as these do and elicit similar changes in the surrounding tissue. The attributes and potentialities of the papilloma will be further considered in Papers II and III.